The Roles of Plant Growth Promoting Microbes in Enhancing Plant Tolerance to Acidity and Alkalinity Stresses - Msimbira, Levini A.; Smith, Donald L. (Frontiers in Sustainable Food Systems, 2020)
Plant growth often occurs under a range of stressful conditions, including soil acidity and alkalinity. Hydrogen ion concentration, which determines pH of the soil, regulates the entire chemistry of plant nutrient colloidal solutions. Beyond certain levels of pH multiple stresses such as hydrogen ion toxicity, and nutrient imbalance, toxicities and deficiencies are induced in plants. Breeding for stress coupled with suitable agronomic practices has been a way to deal with this situation in agriculture. However, plant growth promoting microbes (PGPM) have shown potential as sustainable plant growth enhancers and have potential to help with a range of environmental stresses. Considering the long-term evolutionary relationships between plants and microbes, it is probable that much remains unknown about potential benefits of microbes that could be harnessed from PGPM. This article reviews the current understanding of acidity and alkalinity stress effects on plants and various approaches have or could address these stresses. This review further provides a detailed account of the current understanding regarding the role of PGPM in acidity and alkalinity stress management, including when agronomic practices and plant breeding are combined. Approaches already evaluated have shown limitations because acidity and alkalinity in soils are gradual and progressive conditions. Greater exploitation of PGPM in this regard, would be interesting to explore as they have the potential to address multiple stresses in a more sustainable fashion. Future crop production will require further breeding for pH stress tolerance, but also implementation of microbial technologies that provide enhanced tolerance to pH stress.